2023
DOI: 10.3390/nu15132874
|View full text |Cite
|
Sign up to set email alerts
|

Sex Specificity in the Mixed Effects of Blood Heavy Metals and Cognitive Function on Elderly: Evidence from NHANES

Abstract: The way that males and females react to environmental exposures and negative impacts on their neurological systems is often different. Although previous research has examined the cognitively impairing effects of solitary metal exposures, the relationship between metal mixtures and cognitive function, particularly when considering an individual’s sex, remains elusive. This study aimed to investigate the sex differences in the association between multiple metal combinations and cognitive function in older Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Therefore, it is crucial to explore the effects of mixed exposure to multiple metals on BMD. Noticeably, sex-specific associations of heavy metals with liver fibrosis, kidney function and cognitive function were observed in previous studies (18)(19)(20).…”
Section: Introductionsupporting
confidence: 53%
“…Therefore, it is crucial to explore the effects of mixed exposure to multiple metals on BMD. Noticeably, sex-specific associations of heavy metals with liver fibrosis, kidney function and cognitive function were observed in previous studies (18)(19)(20).…”
Section: Introductionsupporting
confidence: 53%
“…Previous studies have shown that exposure to Cd can impair cognitive performance both in isolated exposure scenarios and in combination with other environmental chemicals identified through EWAS screening. [24][25][26][27] It is also well known that Cd causes vascular damage and promotes atherosclerosis 88 by generating reactive oxygen species, disrupting sulfhydryl homeostasis, and downregulating nitric oxide. 89 Stroke affects cognitive domains such as attention, memory, and language.…”
Section: Discussionmentioning
confidence: 99%
“…17,21 Several studies have assessed associations between exposures to environmental chemicals and cognitive decline in specific populations. For example, exposures to metals, typically manganese (Mn), 22-24 cadmium (Cd), [24][25][26][27] lead (Pb), [25][26][27] barium (Ba), 24 cobalt (Co), 24 cesium (Cs), 24 and thallium (TI) 24 were reported to increase the risk of low cognitive performance. In addition, higher urinary 3-phenoxybenzoic acid concentrations in adults were associated with cognitive dysfunction 28 and it was observed that butyl benzyl phthalate is a potential cognitive-disrupting compound.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific information indicates that elevated Pb and Cd concentrations impair neurological development and function in human populations. Simultaneous ingestion has several effects on the CNS, and in addition to causing cognitive impairment, it can impact social behavior and be responsible for increased depressive disorders [110][111][112][113], generalized anxiety disorders, panic/agoraphobia, and psychological conditions that could even lead to suicide [114][115][116][117]. Clinical research reports that patients with depressive disorders and panic attacks have high concentrations of Pb and Cd in their system [118].…”
Section: Implication Of Pb and CD Intake On Human Healthmentioning
confidence: 99%